Atrial fibrillation‐associated Connexin40 mutants make hemichannels and synergistically form gap junction channels with novel properties. Issue 8 (20th January 2014) - Patel, Dakshesh; Gemel, Joanna; Xu, Qin; Simon, Adria R.; Lin, Xianming; Matiukas, Arvydas; Beyer, Eric C.; Veenstra, Richard D.
Abstract : Mutations of Cx40 ( GJA5 ) have been identified in people with lone chronic atrial fibrillation including G38D and M163V which were found in the same patient. We used dual whole cell patch clamp procedures to examine the transjunctional voltage ( V j ) gating and channel conductance properties of these two rare mutants. Each mutant exhibited slight alterations of V j gating properties and increased the gap junction channel conductance ( γ j ) by 20–30 pS. While co‐expression of the two mutations had similar effects on V j gating, it synergistically increased γ j by 50%. Unlike WTCx40 or M163V, G38D induced activity of a dominant 271 pS hemichannel.